Avantgarda 20.-30. let - Praha a Moskva - Dofková, Jekaterina (Vysoké učení technické v Brně. Fakulta architektury)
Vztahy mezi českou a ruskou avantgardou nebyly dosud řádně prozkoumány, a proto cílem tohoto výzkumu bylo pochopení skutečných faktů a odhalení „bílých míst“, spojených se svérázným rozvojem avantgardní architektury v Československu a SSSR. Pomoci komparativní a historiografické analýzy, se vytvořila celková více či méně podrobná rekonstrukce dějin meziválečného období, jež byla mnohdy opačně interpretována pod politickým tlakem sovětského režimu. Disertace analyzuje vliv politického režimu na architekturu, určuje reflexi dění v sovětském svazu na názory československých architektů, prostřednictvím svědectví o vzájemných kontaktech, vzájemné kritiky a spolupráci v oblasti architektury. Práce shrnula a přinesla nové informací ohledně českých architektů, již projektovali pro SSSR, nebo rovněž tam působili. Výzkum se zakládá na archivních dokumentech, článcích ve specializovaných soudobých časopisech, polemice mezi českými a ruskými architekty.

The relationship between Czech and Russian avantgarde has not been properly examined, therefore the aim of this research was to understand the real facts and uncover “ the blind spots“ connected with the specific development of avantgarde architecture in Czechoslovakia and Soviet Union. A comprehensive and moreless thorough detailed reconstruction of the interwar period has been created with the help of comparative and historiographic analysis. This period used to be interpreted quite contrarily under the political pressure of the Soviet regime. The thesis analyses the influence of the political regime on architecture, determines the reflection of the events in the Soviet Union on the opinions of Czechoslovak architects by means of testimonies about mutual contacts, mutual criticism and cooperation in the sphere of architecture. The thesis brings and concludes new information regarding Czech architects who were designing and working in the Soviet Union. The research is based on archive documents, articles from specialized contemporary magazines and debates between Czech and Russian architects.
The 20' s and 30' s avant-garde - Prague and Moscow
Keywords: Avantgardní architektura; Rusko; Československo; SSSR; Lubomír Šlapeta; Antonín Urban; František Sammer; Jaromír Krejcar; Josef Špalek; Vladimír Němeček; Jan Hromada; Avantgarde architecture; Russia; Czechoslovakia; USSR; Lubomír Šlapeta; Antonín Urban; František Sammer; Jaromír Krejcar; Josef Špalek; Vladimír Němeček; Jan Hromada.